Soybean meal substitution by torula yeast (Candida utilis) grown on vinasses in pelleted diets for fattening rabbits - Ortiz, Abel; Motta Ferreira, W.; Anchieta Ramirez, M.; Moraes Hosken, F.; Lezcano, Pedro (Cuban Journal of Agricultural Science, 2013)
Four diets were evaluated in fattening rabbits of the White New Zealand breed. A completely randomized design with four treatments and 16 replications was used. Treatments consisted of the inclusion in the feed of 0, 5, 10 and 15% of torula yeast (Candida utilis) grown on vinasses from alcohol distillery, as soybean meal substitution. After 41 fattening days, the viability (75.00; 87.50; 93.75 and 87.50 %, respectively), live weight at slaughter (2204; 2233, 2193 and 2228 g/animal), average daily gain (37.49; 38.18; 37.40 and 38.03 g/animal), consumption (4912; 4985; 4946 and 4944 g/animal) and conversion (3.24; 3.20; 3.25 and 3.19) did not differ significantly between treatments. The same occurred with the weight and carcass yield, skin, liver, heart and kidneys. It is concluded that diets for fattening rabbits including torula yeast grown on vinasses from alcohol distillery, as partial or total substitute of soybean meal, do not provoke significant changes in the bio-productive indicators of the rabbits at the end of fattening neither on weight and carcass yield and edible organs after slaughter. Key words: rabbits, feeding, torula yeast